Persepsi Masyarakat Kampung Babakan Ciparay Terhadap Sistem Bagi Hasil (Mudharabah) pada Bank Syariah - Fatah, Amir; Heri, Deden (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The profit sharing system (mudharabah) is a sharia banking product that offers higher profits compared to conventional banking products. However, there are still many people who do not understand the concept of mudharabah, giving rise to negative perceptions of this system. This research aims to analyze the perception of the people of Babakan Ciparay Village towards the profit sharing (mudharabah) system in sharia banks. This research uses a survey method with a purposive sampling technique. The research sample consisted of 10 people who were selected based on certain criteria. Research data was collected through observation, interviews and analyzed using descriptive statistics Perception is a view or opinion formed in a person's mind about something. Society is a group of people who live in one place and have similarities in terms of ethnicity, language, religion and culture. The profit sharing system is a sharia banking system that provides profits to customers and banks based on mutually agreed business results. Mudharabah is a type of profit sharing system applied in sharia banking. Sharia banks are banks that operate based on Islamic sharia principles. The results of the research show that the perception of the people of Babakan Ciparay Village towards the profit sharing (mudharabah) system in sharia banks is still not positive. This is indicated by the perception that this system is high risk, complicated and not transparent. Apart from that, people still do not understand in depth the concept of mudharabah.